Lie. apgėlaĩ, ãpgėlės, apgė́los ir kt. - Buivydienė, Rūta (Baltistica, 2001)
LITH. apgėlaĩ, ãpgėlės, apgė́los ETC. The ethnographic terms Lith. apgėlaĩ, ãpgėlės, apgė́los ‘a ritual visit to a woman that has given birth to a child, as well as the presents given and the refreshments offered on the occasion’ (LKŽ I2 194), up to now have not been discussed anywhere from the viewpoint of word-formation and origin. These words seem to be, in the author’s opinion, terms with various endings derived from the prefixed verb apgélti (àpgelia, apgė́lė). Concerning their semantic motivation, they are to be explained first as “ritual celebration of the end of birth pain (gėlà), as well as the presents given on the occasion” (cf. another related prefixal derivative ãtgėlos ‘a several days’ rest after child-birth’ (= ‘the recession, the end of the birth pain’) (: atgélti, atgė́lė) and belong with the other terms of ritual celebrating the completion of something, terms, which are derived from prefixal verbs by means of endings, cf. ãpbangos ‘ritual feast celebrating the end of something’, ãpminos ‘feast celebrating the completion of flax dressing’, ãpkulos ‘feast celebrating the completion of the thrashing season’, etc. The linking of apgėlaĩ, as well as other word-formative and morphological variants of this word to the verb apgélti is also supported by the verbal noun pagėlaĩ ‘a humid, cold, bitter weather; freezing’, also related to the verb gélti, only derived from the prefixal verb pagélti (pagė́lė) based on another meaning of the verb – ‘to freeze (up to piercing pain)’. The article discusses the oldest written sources of the ethnographic terms in question (these lists are complemented by 17lh century manuscript dictionaries). The content of the apgėlai custom is described on the basis of ethnographic data and written sources of the 17th and 18th cc, whereas the origins of the words apgėlaĩ, ãpgėlės, and apgė́los are explained in the broad context of the word-formation system of the Lithuanian language. The origins and word-formative properties of the main synonymous terms for the custom radỹnos, patekỹlai, patekė̃lai, patekỹnos, patekaĩ, palankỹnos are also discussed. The verb apgėlė́ti (-ė́ja, -ė́jo) ‘to visit a woman recently confined, and to bring presents to her’ (LKŽ I2 194) represents, in the author’s opinion, a desubstantival verb, formed with the suffix -ėti from the noun apgėlaĩ (or ãpgėlės, apgė́los); from the viewpoint of word-formative motivation this secondary verb means ‘to participate in the rite of apgėlaĩ’, cf. also the desubstantival verbs atlaidúoti ‘take part in atlaidaĩ (: atlaidaĩ ‘a church festival of indulgence’), atmeiláuti ‘take part in ãtmeilės (: ãtmeilės ‘a certain rite after marriage’).